2009
DOI: 10.1007/s00425-009-0933-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel insight into the regulation of light-independent chlorophyll biosynthesis in Larix decidua and Picea abies seedlings

Abstract: Light-independent chlorophyll (Chl) biosynthesis is a prerequisite for the assembly of photosynthetic pigment-protein complexes in the dark. Dark-grown Larix decidua Mill. seedlings synthesize Chl only in the early developmental stages and their Chl level rapidly declines during the subsequent development. Our analysis of the key regulatory steps in Chl biosynthesis revealed that etiolation of initially green dark-grown larch cotyledons is connected with decreasing content of glutamyl-tRNA reductase and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…This is probably because these organisms do not accumulate a high level of Pchlide in darkness, and accordingly, they do not need a large amount of POR in darkness. The expression patterns of the genes encoding the DPOR subunits (ChlL, ChlN, and ChlB) in response to light conditions are varied among plant species (Demko et al 2009;Skinner and Timko 1999;Suzuki et al 2001). Meanwhile, in adult Arabidopsis plants, PORA and PORB show circadian rhythmic expression patterns that are similar to the lightinducible Chl synthesis genes, although the oscillation peak is somewhat delayed (Matsumoto et al 2004).…”
Section: Coordinated Transcriptional Regulation Of Chl Biosynthesismentioning
confidence: 99%
“…This is probably because these organisms do not accumulate a high level of Pchlide in darkness, and accordingly, they do not need a large amount of POR in darkness. The expression patterns of the genes encoding the DPOR subunits (ChlL, ChlN, and ChlB) in response to light conditions are varied among plant species (Demko et al 2009;Skinner and Timko 1999;Suzuki et al 2001). Meanwhile, in adult Arabidopsis plants, PORA and PORB show circadian rhythmic expression patterns that are similar to the lightinducible Chl synthesis genes, although the oscillation peak is somewhat delayed (Matsumoto et al 2004).…”
Section: Coordinated Transcriptional Regulation Of Chl Biosynthesismentioning
confidence: 99%
“…They demonstrated the presence of two C to U editing sites in the central region of chlB transcript in P. sylvestris and P. abies and one editing site in L. eurolepis. The presence of two editing sites was also detected in L. decidua (Demko et al 2009). Our preliminary results indicate, that these previously described codons of chlB transcripts can be edited also in P. abies calli cells (data not shown).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 77%
“…Enzymatic reduction of Pchlide to Chlide, catalyzed by DPOR enzyme in the dark, represents another regulatory step in the Chl biosynthesis (Fujita 1996). Constitutive expression of plastid genes chlL, chlN and chlB has been reported in photoautotrophically, mixotrophically and heterotrophically cultivated Chlorella protothecoides cells and in various conifer species grown in the dark (Spano et al 1992, Skinner and Timko 1999, Kusumi et al 2006, Shi and Shi 2006, Demko et al 2009). In contrast to previous studies, we observed very low expression of chlLNB genes in darkgrown calli suggesting that chlLNB expression can be modulated by light in P. abies calli.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 97%
See 1 more Smart Citation
“…However, darkness promotes etiolation in the seedlings of angiosperms because they lack DPOR genes. Consequently, the distribution of DPOR and LPOR entails that the two systems coexisted throughout evolution from the cyanobacteria to the gymnosperms but that the genes encoding DPOR subunits were lost during the evolution from gymnosperms to angiosperms and, as a result, lost their ability to green in the dark (Shi and Shi, 2006;Demko et al, 2009). Hence, the reduction of protochlorophyllide to chlorophyllide in the absence of light in most dark-grown organisms, other than etiolated angiosperms, correlates with the presence of the ChlL, ChlN, and ChlB genes (Shi and Shi, 2006).…”
Section: Introductionmentioning
confidence: 99%